Astragalus Polysaccharides Alleviate Type 2 Diabetic Rats by Reversing the Expressions of Sweet Taste Receptors and Genes Related to Glycolipid Metabolism in Liver - Luo, Meng-Juan; Wang, Ying; Chen, Si-Yu; Yang, Ze-Min (Frontiers in Pharmacology, 2022)
Sweet taste receptors (STRs) play an important role in glucose metabolism, and type 2 diabetic rats have abnormal expressions of STRs in multiple tissues. Astragalus polysaccharides (APS) has shown a significant therapeutic effect on type 2 diabetes mellitus (T2DM), but its mechanism needs to be further clarified. T2DM rat model was induced by intraperitoneal streptozotocin (STZ) injection and treated with APS for 8 weeks. Using the method of non-targeted metabolomic analysis based on Liquid Chromatography-Mass Spectrometry (LC-MS) to determine the main components of APS powder. Western blotting analysis was used to determine the levels of protein expression, and real-time quantitative PCR analysis was used to detect the levels of gene expression. Gene expression analysis found that APS significantly increased the expressions of signaling molecules in sweet taste receptors (STRs) pathways, including taste receptor family 1 member 2 (T1R2), α-gustducin (Gα) and transient receptor potential cation channel subfamily member 5 (TRPM5), and reversed the expressions of genes related to glucolipid metabolism, including glucose transporters 2 and 4 (GLUT2 and GLUT4), pyruvate carboxylase (PC), fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) in the liver of T2DM rats. However, APS had no influences on the expressions of genes, including glycogen synthase kinase-3 beta (GSK-3β), pyruvate kinase (PK) and phosphoenolpyruvate carboxykinase (PEPCK) in the liver of T2DM rats. These results suggested that the physiological roles of STRs in the liver were involved in glucose transport and metabolism. The present study revealed that APS alleviated the symptoms of type 2 diabetes mellitus (T2DM) rats, improved HOMA-IR and promoted insulin secretion. APS alleviated T2DM rats by activating the STRs pathway, and promoted glucose transport and lipogenesis.